Comparative analysis of surgical treatment of patients with locally advanced tumors right anatomical segment of pancreas - Kopchak, V. M.; Shkarban, V. P.; Pererva, L. O.; Savitskiy, A. O.; Kropelnitskiy, V. O.; Bylik, I. I.; Maslyuk, Yu. I.; Mihalchevskiy, V. P. (Modern medical technology, 2023)
Radical resection of pancreas during pancreatic ductal adenocarcinoma has a favorable effect on the patient’s survival rate and disease prognosis. Performance of PV/SMV resection during pancreatoduodenectomy is a routine procedure in leading pancreatology centers, increasing the possibility of R0 resections. Purpose of the study. Is to evaluate the criteria for the diagnosis of vascular invasion at the preoperative stage, to increase the proportion of R0 resections. The study included 73 patients with locally advanced tumors of the pancreatic head operated on in the pancreatic surgery department from 2019 to 2022. The range of operations included: Whipple pancreatoduodenectomy, pyloruspreserving pancreatoduodenectomy, and total pancreatoduodenectomy. The presence or suspicion of vascular invasion, the size, and the stage of the tumor at the preoperative stage were diagnosed according to the data of MSCT, MRI, ultrasonography, and endosonography. Histological examination was carried out according to the recommendations of the College of American Pathologist 2020. The first group 44 of patients who were made pancreatoduodenectomy with resection of PV/SMV, and the second group 29 patients without vascular resection. In the second group, a positive venous (smv) resection margin, R1 resection, had all patients according to the planned histological examination. During the preoperative examination, vascular invasion was suspected in 68,2% of patients in the first group, and 58.6% in the second, 58,6%, (x2 = 0,696; p = 0,403). According to histological examination, damage to the vascular wall was confirmed in 81,8% of cases among the first group of patients. A comparative assessment of the indicators of the two groups indicates that there is no significant difference in tumor size (t = 1,38; p = 0,085), localization, intraoperative data (operation time) (t = 1,19; p = 0,117), the number of postoperative complications (x2 = 0,027; p = 0,869), and the histological type of the tumor. Only intraoperative blood loss had statistical significant. Conclusions. The nowaday preoperative examination protocol allows diagnosing vascular or suspicion of it with sufficient probability and planning adequate surgical intervention. Performing a resection of PV/SMV during pancreaticoduodenectomy with pre- or intraoperative suspicion of vascular invasion allows to increase the number of R0 resections and improve the prognosis of the disease.